2022
DOI: 10.3390/foods11172553
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Leaf Tea from El Salvador: On-Site Production Considering Influences of Processing on Chemical Composition

Abstract: The production of coffee leaf tea (Coffea arabica) in El Salvador and the influences of processing steps on non-volatile compounds and volatile aroma-active compounds were investigated. The tea was produced according to the process steps of conventional tea (Camellia sinensis) with the available possibilities on the farm. Influencing factors were the leaf type (old, young, yellow, shoots), processing (blending, cutting, rolling, freezing, steaming), drying (sun drying, oven drying, roasting) and fermentation (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…The DCM‐L fraction contained the highest content of caffeine (303.04–769.41 mg/g extract), whereas the H 2 O‐L fractions contained the lowest caffeine (0.36–5.24 mg/g extract). The content of caffeine is related to the varieties of plants, age of leaves, tea‐processing methods, and seasonal variation (Deka et al., 2021; Steger et al., 2022). Chen et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCM‐L fraction contained the highest content of caffeine (303.04–769.41 mg/g extract), whereas the H 2 O‐L fractions contained the lowest caffeine (0.36–5.24 mg/g extract). The content of caffeine is related to the varieties of plants, age of leaves, tea‐processing methods, and seasonal variation (Deka et al., 2021; Steger et al., 2022). Chen et al.…”
Section: Resultsmentioning
confidence: 99%
“…whereas the H 2 O-L fractions contained the lowest caffeine (0.36-5.24 mg/g extract). The content of caffeine is related to the varieties of plants, age of leaves, tea-processing methods, and seasonal variation (Deka et al, 2021;Steger et al, 2022). Chen et al (2018) found that young coffee leaves have higher caffeine than mature leaves due to the decreased biosynthesis of caffeine in matured and aged leaves.…”
Section: Processing Methods Age Of Leaves and Extraction Solvents Int...mentioning
confidence: 99%
“…It is rich in chlorogenic acid, catechin, and other polyphenols, suggesting its beneficial effect on health. 12 However, its effect on hyperuricemia and HN remains to be investigated.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Coffee leaf tea can contain up to 80 mg/L caffeine, 100 mg/L chlorogenic acid, and 700 mg/L epigallocatechin gallate. 12 Compared to traditional tea (Camellia sinensis), coffee leaf tea is higher in polyphenols and antioxidants. 13 It has traditionally been used to alleviate various diseases or disorders such as anemia, edema, asthenia, diarrhea, intestinal pain, and fever.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation